What Google’s winning Go algorithm will do next - Gibney, Elizabeth (Nature (London), 2016)
Following the defeat of one of its finest human players, the ancient game of Go has joined the growing list of tasks at which computers perform better than humans. In a 6-day tournament in Seoul, watched by a reported 100 million people around the world, the computer algorithm AlphaGo, created by the Google-owned company DeepMind, beat Go professional Lee Sedol by 4 games to 1. The complexity and intuitive nature of the ancient board game had established Go as one the greatest challenges in artificial intelligence (AI). Now the big question is what the DeepMind team will turn to next.